La2O3 Catalyzed C–C Coupling of Aryl Iodides and Boronic Acids. (18th November 2012) - Malik, Payal; Chakraborty, Debashis
Abstract : An efficient La2 O3 -catalyzed new route for the carbon-carbon bond formation in particular, symmetrical and unsymmetrical biphenyls has been developed, which proceeds through carbon-carbon coupling reaction of aryl iodides with boronic acids. The reaction provided the desired products in moderate-to-good yields with a wide range of functional group tolerance.